2005
DOI: 10.1111/j.1365-2567.2005.02245.x
|View full text |Cite
|
Sign up to set email alerts
|

Tolerosome‐induced oral tolerance is MHC dependent

Abstract: SummaryOral administration of a protein antigen generates a serum factor that induces tolerance when transferred into naïve recipients. This serum factor has been described in rats as consisting of exosome-like structures or tolerosomes, which express major histocompatibility complex class II molecules (MHCII) and mediate antigen-specific tolerance. In this study, we investigated the functions of serum-derived tolerosomes both in vivo and in vitro. Tolerosomes were purified from the 100 000 g pellet fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 41 publications
4
72
0
4
Order By: Relevance
“…This process does not function in the absence of T cells [35], is reduced in efficiency in germ-free mice [4,36] and is dependent on the expression of MHC class II molecules in the intestinal epithelium [37]. SEA feeding induces a massive secretion of IFN-g from IEL, leading to up-regulation of heat shock proteins and MHC class II on the intestinal epithelium [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This process does not function in the absence of T cells [35], is reduced in efficiency in germ-free mice [4,36] and is dependent on the expression of MHC class II molecules in the intestinal epithelium [37]. SEA feeding induces a massive secretion of IFN-g from IEL, leading to up-regulation of heat shock proteins and MHC class II on the intestinal epithelium [38].…”
Section: Discussionmentioning
confidence: 99%
“…Tolerogenic processing involves coupling of dietary antigen peptides to MHC class II molecules within the intestinal epithelial cell and export of the complex on membranous vesicles called tolerosomes [37,39]. The tolerosomes can be isolated from the blood shortly after feeding of an antigen and induce tolerance upon transfer into naïve recipients [40].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes derived from immature DCs expressing immunomodulatory cytokines and ligands (i.e., IL-10, IL-4, FasL) have shown a beneficial effect on delayed-type hypersensitivity and inflammation in animal models (Ostman et al, 2005;Tamura et al, 2012).…”
Section: Applications Of Extracellular Membrane Vesicles For Clinicalmentioning
confidence: 99%
“…19,20 The tolerogenic effect of serum obtained shortly after an antigen feed was first described by Strobel et al 6 using a Th1 sensitization as read-out; however, despite great efforts the nature of the tolerizing serum factor was not revealed until recently. 18,20,21 We also monitored the involvement of regulatory T cells in the induction of tolerance in the present model. As described in our results we found a higher frequency of activated CD4 + T cells with a regulatory phenotype in the group receiving the tolerogenic serum.…”
Section: Discussionmentioning
confidence: 99%
“…8 Moreover we have shown that this exosome-mediated tolerance is MHC class II dependent and requires an intact immune system in the fed donor. 18 In the present study we wanted to investigate whether serum-derived exosomes from antigen-fed donors could also protect against allergic airway inflammation in a mouse model of allergic asthma.…”
Section: Introductionmentioning
confidence: 99%